2017
DOI: 10.20472/ss2017.6.1.003
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Relationship Between Lifestyle and Attitude Towards Death: The Case of Kerman Middle-Aged Adults

Abstract: It is obvious that the most personal and most probable inner reality of human beings is death

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
(7 reference statements)
0
0
0
Order By: Relevance
“…Similar studies have also found a negative relationship between the meaning in life and DA (Yoon, 2009;Yüksel et al, 2017). In another study, a negative significant relationship was found between DA and attitude towards life (Azarian et al, 2016). There are studies reporting a negative relationship between fear of death and the purpose in life (Ardelt, 2008;Viswanathan, 1996).…”
Section: Discussion Conclusion Recommendationsmentioning
confidence: 67%
“…Similar studies have also found a negative relationship between the meaning in life and DA (Yoon, 2009;Yüksel et al, 2017). In another study, a negative significant relationship was found between DA and attitude towards life (Azarian et al, 2016). There are studies reporting a negative relationship between fear of death and the purpose in life (Ardelt, 2008;Viswanathan, 1996).…”
Section: Discussion Conclusion Recommendationsmentioning
confidence: 67%